Simulação computacional da interação de quitosana com o herbicida glifosato para descontaminação ambiental - Faria, Roberto Ribeiro (2015)
The quality and clarity of water consist of an attractive problematic, since they relate to the maintenance of the biosphere, as water is one of the essential factors for the existence of life on earth. However, human actions cause several types of environmental depletion, as contamination by herbicides, which is an anthropogenic result which can cause poisoning of living beings with severe complications such as neurological problems, cancer, birth defects and endocrine disorders. Brazil, the largest exporter of coffee, sugar cane, orange juice and soy, has become the largest consumer of world\'s pesticides, with 1/3 of Brazilian food contaminated by these substances. The possibility of mitigate environmental impacts of herbicides is very important and can be accomplished through appropriate treatment in contaminated water. Thus, the present work relates to the study of the interaction between the most commercialized herbicide over the world, glyphosate, and very abundant biopolymer in nature, chitin and chitosan derivative thereof, which have use in the adsorption of various environmental contaminants. Using molecular dynamics simulations for the analysis of chemical interactions between the two species at atomic level was of great value, in such a way that experimental physical-chemical parameters acted in an attempt to \"approximate\" the theoretical computations of actual / experimental procedures. The molecular dynamics simulations allowed the description of the microscopic behavior of α- and β- filaments chitin and chitosan in aqueous solution as well as the identification of the more stable polymorphic forms, identification of the functional groups responsible for these biopolymers herbicide adsorption process glyphosate, as well as the interaction of most representative one, the calculation of the intensity of herbicide-polysaccharide interaction forces, the importance of the hydrogen interactions of the herbicide adsorption process. Thus, this study served as a pioneer in the use of chitosan for environmental decontamination of the herbicide glyphosate.